ANALISIS KEMAMPUAN LITERASI SAINS SISWA SMP MENGGUNAKAN METODE NATURE OF SCIENCE LITERASY TEST (NOSLiT) DI KABUPATEN KONAWE SELATAN - Hasnawati, Hasnawati; Saranani, M. Safiuddin; Lasaima, Ordiman; Syarifuddin, Syarifuddin (Fakultas Pertanian Universitas Halu Oleo, 2023)
Scientific literacy is seen not only as an important component of science education, but also as an ethical/moral competency. Science education plays an important role in creating responsible citizens, in this case scientific literacy is needed in making social-scientific decisions. Currently, the concept of scientific literacy has become a learning goal in educational curricula in various countries. Scientific literacy emphasizes students' ability to analyze, predict, and apply scientific concepts in everyday life. Likewise with students in South Konawe district at junior high school level, the majority of whose scientific literacy skills are classified as poor. The aim of this research is to determine the scientific literacy abilities of junior high school students using the Nature of Science Literacy Test (NOSLiT) method in South Konawe Regency. The research method used in this research is quantitative with a descriptive approach. The sampling technique in this research used a simple random sampling technique. The results of this research show that the scientific literacy abilities of South Konawe Middle School students based on the NOSLiT instrument in class IX are still in the low category while for class VII and class VIII they are classified as very low. This can be seen from the overall average NOSLiT scores for all grade levels, namely 37%, 39.4% and 45.5%, respectively. Then, after calculating it as a whole, it was obtained that the average percentage of scientific literacy abilities of South Konawe Middle School students was in the low category, namely 40.8%. The scientific literacy achievement for the NOSLiT indicator of South Konawe Middle School students at all grade levels obtained the highest percentage of achievement in the aspect of scientific naming, followed by the aspect of scientific misconceptions, and process skills ability and the lowest percentage of achievement was in the aspect of scientific postulates. The highest achievement for all NOSLiT indicators in general was obtained by class IX, then followed by class VIII and class VII. The achievement percentage obtained by class IX for indicators of scientific naming, process skill abilities and main misconceptions reached 50% and was above 50% but still This percentage is still in the low category.